D-Dimer as Biomarker for Early Prediction of Clinical Outcomes in Patients With Severe Invasive Infections Due to Streptococcus Pneumoniae and Neisseria Meningitidis - Meini, Simone; Sozio, Emanuela; Bertolino, Giacomo; Sbrana, Francesco; Ripoli, Andrea; Pallotto, Carlo; Viaggi, Bruno; Andreini, Roberto; Attanasio, Vittorio; Rescigno, Carolina; Atripaldi, Luigi; Leonardi, Silvia; et al. (Frontiers in Medicine, 2021)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection; no current clinical measure adequately reflects the concept of dysregulated response. Coagulation plays a pivotal role in the normal response to pathogens (immunothrombosis), thus the evolution toward sepsis-induced coagulopathy could be individuate through coagulation/fibrinolysis-related biomarkers. We focused on the role of D-dimer assessed within 24 h after admission in predicting clinical outcomes in a cohort of 270 patients hospitalized in a 79 months period for meningitis and/or bloodstream infections due to Streptococcus pneumoniae (n = 162) or Neisseria meningitidis (n = 108). Comparisons were performed with unpaired t-test, Mann-Whitney-test or chi-squared-test with continuity correction, as appropriate, and multivariable logistic regression analysis was performed with Bayesian model averaging. In-hospital mortality was 14.8% for the overall population, significantly higher in S. pneumoniae than in N. meningitidis patients: 19.1 vs. 8.3%, respectively (p = 0.014). At univariable logistic regression analysis the following variables were significantly associated with in-hospital mortality: pneumococcal etiology, female sex, age, ICU admission, SOFA score, septic shock, MODS, and D-dimer levels. At multivariable analysis D-dimer showed an effect only in N. meningitidis subgroup: as 500 ng/mL of D-dimer increased, the probability of unfavorable outcome increased on average by 4%. Median D-dimer was significantly higher in N. meningitidis than in S. pneumoniae patients (1,314 vs. 1,055 ng/mL, p = 0.009). For N. meningitidis in-hospital mortality was 0% for D-dimer <500 ng/mL, very low (3.5%) for D-dimer <7,000 ng/mL, and increased to 26.1% for D-dimer >7,000 ng/mL. Kaplan-Meier analysis of in-hospital mortality showed for N. meningitidis infections a statistically significant difference for D-dimer >7,000 ng/mL compared to values <500 ng/mL (p = 0.021) and 500–3,000 ng/mL (p = 0.002). For S. pneumoniae the mortality risk resulted always high, over 10%, irrespective by D-dimer values. In conclusion, D-dimer is rapid to be obtained, at low cost and available everywhere, and can help stratify the risk of in-hospital mortality and complications in patients with invasive infections due to N. meningitidis: D-dimer <500 ng/mL excludes any further complications, and a cut-off of 7,000 ng/mL seems able to predict a significantly increased mortality risk from much <10% to over 25%.